Kinematics of Stewart Platform Explains Three-Dimensional Movement of Honeybee's Abdominal Structure. Issue 3 (15th May 2019) - Liang, Youjian; Zhao, Jieliang; Yan, Shaoze; Cai, Xin; Xing, Yibo; Schmidt, Alexander
Abstract: The Stewart platform is a typical parallel mechanism, used extensively in flight simulators with six degrees of freedom. It is rarely found in animals and has never been reported to regulate and control physiological activities. Now an equivalent Stewart platform structure is found in the honey bee (Hymenoptera: Apidae: Apis mellifera L.) abdomen to explain its three-dimensional movements. The stereoscope and scanning electron microscope are used to observe the internal structures of honeybees' abdomens. Experimental observations show that the muscles and intersegmental membranes connect the terga with the sterna and guarantee the honey bee abdominal movements. From the perspective of mechanics, a Stewart platform is evolved from the lateral connection structure of the honey bee abdomen, and the intrasegmental muscles between the sternum and tergum function as actuators between planes of the Stewart platform. The extraordinary structure provides various advantages for a honey bee to complete a variety of physiological activities. This equivalent Stewart platform structure can also be used to illustrate the flexible abdominal movements of other insects with the segmental abdomen.